Developing a solid phase microextraction method for the identification of accelerants in fire debris / Abdul Aziz Haron and Nor'ashikin Saim - Haron, Abdul Aziz; Saim, Nor'ashikin (Faculty of Applied Sciences, 2005)
Solid Phase Microextraction (SPME) method of identifying accelerants from fire debris is developed. Experimental design methodology was used to evaluate the simultaneous effect of SPME operating variables (extraction time, extraction temperature, desorption time) on the extraction of target analytes (benzene, toluene, xylene and hexadecane). The results showed that extraction temperature and extraction time were the more significant factors. Optimum operating conditions for SPME were determined using a response surface method. The results indicate that SPME is capable of analyzing accelerants from fire debris.